Estrés Parental y Dinámica Familiar (2023)
The following degree project aimed to evaluate the effects of parental stress on family dynamics (affectivity, communication and authority) of adolescent of the district of Buenaventura Valle. For the collection of information, a first stage was carried out in which quantitative data were collected and analyzed, which were collected through the application of the scale on parental stress (PSI - SF) Abidin (1995) being the results of this those that allowed the collected through the technique of semi-structured interview.